Peran Citra Destinasi dan Perilaku Konsumen dalam Mempengaruhi Keputusan Konsumen dalam Memilih Destinasi Halal - Handayani, Susi; Hasibuan, Lailan Safina; Bismala, Lila (BISNIS, 2021)
Tourism is one of the largest service industries and provides opportunities and hope for any destination to capitalize on it, create jobs and support other sectors. The demographics of the young and large Muslim market, the rapid economic growth of Muslim-majority countries, Islamic values encourage the growth of Islamic business and lifestyle, the growth of trade transactions between Organization of the Islamic Conference (OIC) countries, are the motors of the growth of the global Muslim market. This is what encourages the emergence of halal tourism. The purpose of the study was to examine the effect of destination image and consumer behavior on consumer decisions in choosing halal destinations. The number of samples in this study were 150 respondents. The data analysis technique used in this study is multiple regression analysis to examine the partial and simultaneous effect of destination image and consumer decisions on consumer decisions in choosing halal destinations. The results showed that partially the image of the destination and consumer behavior had a negative effect on consumer decisions in choosing halal destinations. Meanwhile, simultaneously, destination image and consumer behavior have a positive effect on consumer decisions in choosing halal destinations. This shows that simultaneously, the image of a destination owned by a halal destination and consumer behavior influence consumer decisions in choosing a halal destination, so it is very important to maintain the image of the halal destination, so that it really shows halal in the true sharia aspect. Keywords: Consumer Behavior, Consumer Decision, Destination Image